1998
DOI: 10.1177/0893318998113004
|View full text |Cite
|
Sign up to set email alerts
|

Employee Attitudes Regarding Electronic Mail Policies

Abstract: This study investigates employee attitudes toward e-mail and e-mail policies through a case study of e-mail users at a major university libmry. The study employs a triangulation methodology (interviews, questionnaires, and focus groups) to determine how the employees use e-mail, what problems they have with it, and how they feel about policies for e-mail management. Results indicate strong differences in attitudes based on job position (faculty, professional, and classified) and frequency of e-mail usage. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 29 publications
1
9
0
Order By: Relevance
“…The ability to leave a message, contact those outside the department, and gain an appreciation of the bigger picture increased organizational and departmental awareness. Participants became more engaged with others in the communication process and were consequently able to develop and maintain relationships that may not otherwise have occurred, which is consistent with the findings of Hacker et al (1998) who envisaged e-mail as a relationship-building tool. Although positive outcomes can be identified for communication, negative consequences were also apparent.…”
Section: Positive-unintended Consequencessupporting
confidence: 88%
See 2 more Smart Citations
“…The ability to leave a message, contact those outside the department, and gain an appreciation of the bigger picture increased organizational and departmental awareness. Participants became more engaged with others in the communication process and were consequently able to develop and maintain relationships that may not otherwise have occurred, which is consistent with the findings of Hacker et al (1998) who envisaged e-mail as a relationship-building tool. Although positive outcomes can be identified for communication, negative consequences were also apparent.…”
Section: Positive-unintended Consequencessupporting
confidence: 88%
“…The second explanation concerns compensating for the lack of non-verbal cues by using more relational communication characterized through irony. In the sense of relationship building, some employees have found that being able to initiate contact with other employees via e-mail is much simpler (and perhaps more importantly, less intimidating) than using the telephone or introducing themselves to someone unknown (Hacker et al, 1998). The creation of relational communication is a key aspect when investigating how email and F2F communication complement each other or are divergent.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Personal attributes are important indicators of technology adoption [10], [13], [23], [27], [36], [57], [60]. For instance, senior people may find it harder to adopt new technologies than younger people because of the substantial learning effort required [20], [57].…”
Section: A Personal Characteristics Relatedmentioning
confidence: 99%
“…Rice and Shook [49] postulated the positive association between the usage of electronic messaging system (EMS) and quality of work, and between the usage of EMS and information processing efficiency. Professionals such as software engineers adopting e-mail to support their work may recognize e-mail as more productive than nonprofessionals do [27]. Therefore, we revisited the relationships by suggesting the following.…”
Section: E-mail Use and Outcomes Relatedmentioning
confidence: 99%